Infant feeding and oral health of children ages 2-5 years in Guimbal, Iloilo a cross-sectional study - Acma, Kathleen Ann.; Adolfo, Estee Joy G.; Bautista, Ezekiel Therese S.; Calimot, Andro Dominic A.; Dinopol, Christine Alexis; Gasataya, Charisse Ann.; Ingles, John Wibelle; Legaspi, Marianne C.; Linas, Pearl Joy C.; Lunar, Lanilyn Marie F.; Moises, Rochelle Anne Q.; Yunque, Vanessa Aura. (2015.)
Some studies reported that the breastfeeding and its duration is a protective factor for dental caries in early childhood while some other studies report that it is a risk factor and yet other studies report no association. Similarly, previous studies on the association of the type of infant feeding practices and dental caries in early childhood have produced contradicting results. This community-based comparative cross-sectional study aimed to determine the association between (1) infant feeding practices of three types: exclusive breastfeeding mixed feeding and exclusive bottle feeding and (2) duration of breastfeeding and dental caries among children ages 2-5 years in Guimbal, Iloilo. This study was conducted among randomly selected 188 children ages 2-5 year in Guimbal, Iloilo, all of whom have complete secondary data on dental caries obtained form the Municipal Health Office. Dental caries was considered present if at least one tooth is decayed, missing because of caries or filled based on the criteria of American Academy of Pediatric Dentistry. Primary data on type of infant feeding practices and duration of breastfeeding was collected through an interview schedule using pre-tested questionnaire on the mothers of the subjects. Then, statistical analysis was carried out, controlling biological factors namely sex, parity, maternal age at delivery and socioeconomic factors namely family income, maternal educational attainment and family smoking status as confounders while controlling use of fluoride toothpaste a day time as outcome modifiers. Using logistic regression, it was found out that there is no significant association between the type of infant feeding practices and dental caries (OR=0.601; CI=0.250-1.1442). Similarly, there is also no significant association between the duration of exclusive breastfeeding and dental caries (OR= 0.483; CI= 0.162-1.442) and no significant association between the duration of breastfeeding regardless of exclusivity and dental caries (≤6 months: OR= 1.332, CI=0.212-8.378; 7-12 months: OR=0.946, CI= 0.126-7.092, 13-18 months: OR=1.752, CI=0.187-15.959; >18 months: OR=1.725; CI=0.278-10.695). Furthermore, data gathered on Knowledge, Attitudes, and Practices (KAP) of mothers indicated low levels of knowledge regarding the advantages of breastfeeding and little to no focus on oral care outside of brushing among the mothers interviewed. Thus, the preventive approach of educating parents or primary caregivers of children about dental caries should be encouraged.
Research Project (Undergraduate, Public Health Practice) University of the Philippines Visayas, Miagao,Iloilo
Keywords: Infant feeding